Porous carbon and silicon carbon negative electrode material and preparation method and application thereof
By using porous carbon as a carrier in silicon-carbon anode material and deposition of nano-silicon by vapor phase, the problem of volume change in silicon-carbon anode material during battery charging and discharging is solved, and a high capacity, high first-efficiency and low expansion rate of batteries are achieved Performance improves the cycle stability and safety of the battery.
Patent Information
- Application Number
- CN202411381155.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The volume changes in silicon carbon negative electrode materials during the charging and discharging of the battery lead to damage to the electrode structure, affecting the battery capacity and stability. The existing technology cannot effectively solve this problem.
Porous carbon materials are used as support to deposition of nanosilicon by vapor phase to form a silicon carbon negative electrode material with high microporosity and suitable pore size distribution, reducing volume expansion rate and improving electrochemical stability.
It significantly improves the capacity and first-term effect of silicon-carbon anode material, extends the cycle stability and safety performance of the battery, reduces the volume expansion rate, and improves the overall performance of the battery.
Smart Images

Figure CN119284872A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a porous carbon, silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development of electric vehicles, people's demand for batteries is increasing. Batteries usually contain positive electrodes, negative electrodes and separators. Among them, the negative electrode material in the negative electrode has an important influence on the electrical performance of the entire battery. Silicon-carbon negative electrode material is a new type of negative electrode material developed in recent years. Silicon negative electrode material undergoes huge volume changes during the battery charging and discharging process, which will cause the electrode active material to fall off and pulverize, and even cause damage to the electrode structure, resulting in rapid attenuation of battery capacity, which seriously restricts its industrial application. People usually compound carbon materials with silicon materials to obtain silicon-carbon composite materials in order to achieve the purpose of improving the volume effect of silicon and improving its electrochemical stability. However, the current silicon-carbon negative electrode materials still have technical problems such as unsatisfactory capacity and unsatisfactory improvement of silicon's volume effect.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The first purpose of the present invention is to provide a porous carbon having a high microporosity and a pore size distribution in the range of 1-2 nm, which can effectively improve the loading efficiency of silicon, effectively alleviate the volume expansion of silicon when lithium is embedded, reduce the volume expansion rate of silicon-based negative electrode materials, and improve their capacity and initial efficiency.
[0005] Another object of the present invention is to provide a silicon-carbon negative electrode material having the characteristics of high capacity, high initial efficiency and low volume expansion rate.
[0006] Another object of the present invention is to provide a method for preparing a silicon-carbon negative electrode material, which method is simple and easy to implement.
[0007] Another object of the present invention is to provide an electrode.
[0008] Another object of the present invention is to provide a lithium ion battery.
[0009] Another object of the present invention is to provide an electrical appliance.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] A porous carbon, wherein the porous carbon comprises micropores, and the percentage of the pore volume of the micropores to the total pore volume is greater than or equal to 85%, and in a pore distribution curve obtained by a nitrogen adsorption method, the abscissa is the pore diameter and the ordinate is the differential pore volume dV / dW, the porous carbon has a pore diameter range of 1 to 2 nm, and the differential pore volume dV / dW>0.05 cm 3 ·g -1 ·nm -1 .
[0012] In some embodiments, the porous carbon has at least one peak in the range of pore diameters of 1 to 2 nm.
[0013] In some embodiments, the porous carbon has at least one peak-valley in the range of pore diameters of 1 to 2 nm, and the differential pore volume dV / dW corresponding to the lowest point of the peak-valley is greater than 0.1 cm 3 ·g -1 ·nm -1 .
[0014] In some embodiments, in the porous carbon, the percentage of pore volume with pore diameters less than 0.7 nm in the total pore volume is less than 30%.
[0015] In some embodiments, the pore volume of the porous carbon is 0.7 to 1.2 cm 3 / g.
[0016] In some embodiments, the specific surface area of the porous carbon is 1500 to 2500 m 2 / g.
[0017] In some embodiments, the particle size Dv50 of the porous carbon is 3 to 10 μm, the particle size Dv99 of the porous carbon is 10 to 25 μm, and the particle size Dn10 of the porous carbon is 0.5 to 5 μm.
[0018] In some embodiments, the tap density of the porous carbon is 0.3 to 0.5 g / cm 3 .
[0019] In some embodiments, the porous carbon powder has a conductivity of 0.5 to 10 S / mm.
[0020] In some embodiments, the mass content of elemental oxygen in the porous carbon is less than 2%.
[0021] A silicon-carbon negative electrode material comprises the porous carbon and nano-silicon located in the pores of the porous carbon.
[0022] In some embodiments, the mass content of the nano-silicon in the silicon-carbon negative electrode material is 5 to 85%.
[0023] In some embodiments, the particle size Dv50 of the silicon-carbon negative electrode material is 3 to 10 μm, the particle size Dv99 of the silicon-carbon negative electrode material is 10 to 25 μm, and the particle size Dn10 of the silicon-carbon negative electrode material is 0.5 to 5 μm.
[0024] In some embodiments, the specific surface area of the silicon-carbon negative electrode material is 0.5 to 30 m 2 / g.
[0025] In some embodiments, the tap density of the silicon-carbon negative electrode material is 0.5 to 2 g / cm 3 .
[0026] In some embodiments, the surface of the silicon-carbon negative electrode material further includes a coating layer; the coating layer contains at least one of amorphous carbon, a fast ion conductor and a high molecular polymer.
[0027] The method for preparing the silicon-carbon negative electrode material as described above comprises the following steps:
[0028] The porous carbon is vapor-deposited in an atmosphere containing a silicon source to obtain the silicon-carbon negative electrode material.
[0029] In some embodiments, the method further includes: coating the silicon-carbon negative electrode material to obtain a coating layer on the surface of the silicon-carbon negative electrode material, wherein the coating layer contains at least one of amorphous carbon, a fast ion conductor and a high molecular polymer.
[0030] An electrode comprises the porous carbon, or the silicon-carbon negative electrode material, or the silicon-carbon negative electrode material prepared by the method for preparing the silicon-carbon negative electrode material.
[0031] A lithium ion battery comprises the electrode.
[0032] An electrical appliance comprises the lithium-ion battery.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The porous carbon of the present invention has a high microporosity, and in the range of pore size of 1-2nm, the pore size distribution is a Luan-shaped distribution, which can effectively improve the loading efficiency of silicon, and can reserve a part of space for the nano-silicon cycle process to alleviate the volume expansion caused by the lithium insertion expansion of silicon. It has the effect of alleviating the volume expansion of silicon when lithium is inserted, and can reduce the volume expansion rate of silicon-based negative electrode materials, and improve the capacity and initial efficiency of silicon-carbon negative electrode materials.
[0035] (2) The silicon-carbon negative electrode material of the present invention has the characteristics of high capacity and high initial efficiency, which can improve the cycle stability of the battery.
[0036] (3) The preparation method of the silicon-carbon negative electrode material of the present invention is simple and easy, and the silicon-carbon negative electrode material can be obtained by vapor-depositing a silicon source on porous carbon. The silicon-carbon negative electrode material obtained by this method has the characteristics of high capacity and high initial efficiency, and can improve the cycle performance and safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 : is a pore size distribution curve of the porous carbon in Example 1 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume), which is a Luan-shaped pore;
[0039] Figure 2 is a pore size distribution curve of the porous carbon in Example 2 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume), which is a Luan-shaped pore;
[0040] Figure 3 The pore size distribution curve of the porous carbon in Example 3 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume), which is a Luan-shaped pore;
[0041] Figure 4 It is a pore size distribution curve of the porous carbon in Comparative Example 1 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume), which is a peak-type pore;
[0042] Figure 5 It is a pore size distribution curve of the porous carbon in Comparative Example 2 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume), which is a Luan-shaped pore;
[0043] Figure 6 The pore size distribution curve of the porous carbon in Comparative Example 3 of the present invention (the primary axis of the ordinate is the differential pore volume dV / dW, and the secondary axis is the cumulative pore volume), which is a Luan-shaped pore;
[0044] Figure 7 It is a schematic diagram of Luan-shaped distribution;
[0045] Figure 8 Schematic diagram of the peak distribution. DETAILED DESCRIPTION
[0046] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0047] According to one aspect of the present invention, the present invention relates to a porous carbon, wherein the porous carbon comprises micropores, the pore volume of the micropores accounts for a percentage greater than or equal to 85% of the total pore volume, and in a pore distribution curve obtained by a nitrogen adsorption method, the abscissa is the pore diameter and the ordinate is the differential pore volume dV / dW, wherein the porous carbon has a pore diameter of 1 to 2 nm, and the differential pore volume dV / dW>0.05 cm 3 ·g -1 ·nm -1 .
[0048] That is to say, the pore distribution curve has no intersection with the horizontal axis in the pore diameter range of 1-2nm (excluding the endpoint value) (the pore distribution curve has no intersection with the horizontal axis, which means that the differential pore volume dV / dW ≠ 0), and the pore distribution curve is not close to the horizontal axis in the pore diameter range of 1-2nm (the pore distribution curve is close to the horizontal axis, which means that the differential pore volume dV / dW ≤ 0.05cm 3 ·g -1 ·nm -1 ).
[0049] In the present invention, according to the definition of the International Union of Pure and Applied Chemistry (IUPAC), micropores refer to pores with a pore diameter of less than 2 nm.
[0050] Not bound by theory, basic problems such as the serious volume effect of silicon during the charging and discharging process have seriously hindered the effective use of its advantages. In the porous carbon of the present invention, the pore volume of pores (micropores) with a pore size of less than 2nm accounts for a large percentage of the total pore volume (i.e., microporosity), which can effectively improve the efficiency of silicon loading, reserve a part of the space for the nano-silicon cycle process to alleviate the volume increase caused by the expansion of silicon, and have the effect of alleviating the volume expansion of silicon when lithium is embedded, which can reduce the volume expansion rate of silicon-based negative electrode materials and improve the cycle stability of the battery.
[0051] Not subject to theoretical constraints, pores with a pore size in the range of 1 to 2 nm (excluding the endpoint values) have two types of pore distribution, one is a peak distribution and the other is a Luan-shaped distribution.
[0052] Among them, the peak-type pore structure is mainly manifested in the interval of pore diameter of 1-2nm (excluding the endpoint value), the pore distribution curve has more than one intersection with the horizontal axis or is close to the horizontal axis, and further, in most cases, the peak-type pore structure has at least one peak in the interval of pore diameter of 1-2nm, and / or the porous carbon has at least one peak valley in the interval of pore diameter of 1-2nm, and the lowest point of the peak valley Dv / Dw is less than 0.05cm 3 ·g -1 ·nm -1 The characteristics of peak pore distribution are mainly manifested in that as the pore size increases, the pore distribution changes in a peak-to-valley manner, and the pore size transition is relatively steep. In the peak pore structure, the pore size distribution is discontinuous and the total number of pores is insufficient, such as Figure 8 As shown, the peak-shaped pores will suddenly change in diameter. When the pores are deeper and smaller in diameter, the resistance that nano-silicon has to overcome to enter is greater, and the relative distance that can diffuse (compared to the pore depth) is shorter. Therefore, the utilization rate of the pores is also lower.
[0053] The characteristics of Luan-shaped pore distribution are mainly manifested in that as the pore diameter increases, the pore distribution changes in a mountainous manner, and the pore diameter transition is relatively smooth and gentle. In the pore diameter range of 1-2nm, the pore distribution curve has no intersection with the horizontal axis, nor is it close to the horizontal axis, and the pore distribution is relatively uniform. The pores of the Luan-shaped structure have continuous and uninterrupted pore size distribution, a large number of total pores, and basically consistent pore depths, such as Figure 7 As shown, the Luan-shaped pore depth will not suddenly change in diameter like the peak-shaped pore depth, so the local resistance caused by the change in diameter can be reduced, which is conducive to the entry of vapor-phase silicon precursor molecules (such as silane molecules) and improves the silicon loading efficiency. Porous carbon with the above characteristics is conducive to making silicon carbon have higher capacity and efficiency and lower expansion performance.
[0054] In some embodiments, on the pore size distribution curve of the porous carbon, there is at least one peak in the distribution curve corresponding to the pore size in the range of 1 to 2 nm; and / or, the porous carbon has at least one peak and valley in the pore size range of 1 to 2 nm, and the differential pore volume dV / dW corresponding to the lowest point of the peak and valley is greater than 0.1 cm 3 ·g -1 ·nm -1 including but not limited to 0.11cm 3 ·g -1 ·nm -1 、0.12cm 3 ·g -1 ·nm -1 、0.15cm 3 ·g -1 ·nm -1 , 0.2cm 3 ·g -1 ·nm -1, 0.5cm 3 ·g -1 ·nm -1 etc., or a range between any two of the above.
[0055] In some embodiments, in the porous carbon, the percentage of pore volume of pores with a pore size less than 0.7 nm in the total pore volume is less than 30%. In some embodiments, the percentage of pores with a pore size less than 0.7 nm in the porous carbon includes but is not limited to 1%, 2%, 5%, 8%, 10%, 15%, 20%, 25%, 28%, 29%, etc., or a range between any two of the above. It is difficult for silane molecules to enter the ultra-micropores with a pore size below 0.7 nm during deposition, so it is necessary to limit the percentage of ultra-micropores. The percentage of pores with a pore size less than 0.7 nm in the porous carbon of the present invention is less than 30%, which is more conducive to ensuring the silicon loading efficiency of the porous carbon, so as to facilitate the electrical properties of the silicon-carbon material.
[0056] In some embodiments, the pore volume of the porous carbon is greater than 0.7 cm 3 In some embodiments, the pore volume of the porous carbon includes but is not limited to 0.72 cm 3 / g, 0.75cm 3 / g, 0.8cm 3 / g, 0.85cm 3 / g, 0.9cm 3 / g, 1cm 3 In some embodiments, the pore volume of the porous carbon is 0.7 to 1.0 cm 3 The porous carbon of the present invention has an appropriate pore volume, which is beneficial to ensuring its physical and chemical properties, and is beneficial to the subsequent loading of silicon materials, ensuring that it has an appropriate silicon loading rate, so as to improve the capacity and initial effect of the silicon-carbon composite material.
[0057] In some embodiments, the specific surface area of the porous carbon is 1500 to 2500 m 2 In some embodiments, the specific surface area of the porous carbon includes but is not limited to 1500 m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g, 2000m 2 / g, 2100m 2 / g, 2200m 2 / g、2500m 2 / g, etc., or a range between any two of the above. The porous carbon of the present invention has a suitable specific surface area, which is beneficial to ensure the loading effect on the silicon material.
[0058] In some embodiments, the porous carbon of the present invention has a suitable particle size, and the particle size Dv50 of the porous carbon is 3 to 10 μm, including but not limited to 3 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc., or a range between any two of the above. The particle size Dv99 of the porous carbon is 10 to 25 μm, including but not limited to 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 25 μm, etc., or a range between any two of the above. The particle size Dn10 of the porous carbon is 0.5 to 5 μm, including but not limited to 0.5 μm, 1 μm, 2 μm, 5 μm, etc., or a range between any two of the above.
[0059] In some embodiments, the porous carbon of the present invention has a suitable tap density of 0.3 to 0.5 g / cm 3 In some embodiments, the tap density of the porous carbon includes but is not limited to 0.32 g / cm 3 , 0.33g / cm 3 , 0.35g / cm 3 , 0.38g / cm 3 etc., or a range between any two of the above.
[0060] In some embodiments, the powder conductivity of the porous carbon of the present invention is 0.5 to 10 S / mm. In some embodiments, the powder conductivity of the porous carbon includes but is not limited to 2.2 S / mm, 2.5 S / mm, 2.8 S / mm, 3 S / mm, 3.5 S / mm, 4 S / mm, 5 S / mm, 8 S / mm, 10 S / mm, etc., or a range between any two of the above. The porous carbon of the present invention has a high conductivity.
[0061] In some embodiments, the mass content of elemental oxygen in the porous carbon is less than 2%, including but not limited to 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, etc., or a range between any two of the above.
[0062] In some specific embodiments of the present invention, the porous carbon includes at least one of biomass-derived carbon, resin-derived carbon, petroleum coke-derived carbon, coal-derived carbon, metal-modified carbon materials, and metal oxide-modified carbon materials.
[0063] In some specific embodiments of the present invention, the porous carbon can be selected from commercial specification products, or prepared by methods known in the art, such as hydrothermal method, solvothermal method, electrochemical deposition method, powder metallurgy method, molten metal method, ion exchange method, activation method, etc.
[0064] The method for preparing porous carbon in the specific embodiment of the present invention is described by taking the following method for preparing porous carbon as an example, but is not limited thereto, and any other method for preparing porous carbon may be used.
[0065] The method for preparing the porous carbon comprises the following steps:
[0066] (1) Dry the mangosteen peel and grind it into powder.
[0067] (2) The powder obtained in step (1) is stirred in HCl, then washed with deionized water until the water becomes colorless, and dried.
[0068] (3) The dried mangosteen peel powder and KOH obtained in step (2) are uniformly dispersed in water in a mass ratio of 1:1 to 1:4, stirred, and then freeze-dried to remove moisture.
[0069] (4) In an argon atmosphere, the mixed precursor obtained in step (3) is rapidly heated to 200° C. in a tube furnace, then slowly heated from 200° C. to 550° C., then rapidly heated to 600-1000° C., and heated at 600-1000° C. for 1 h.
[0070] (5) The calcined product is washed with deionized water and vacuum dried to obtain the porous carbon.
[0071] In some specific embodiments of the present invention, in step (4): in an argon atmosphere, the mixed precursor obtained in step (3) is rapidly heated to 200°C at a heating rate of 10°C / min in a tube furnace, then slowly heated from 200°C to 550°C for 10 hours, then rapidly heated to 600-1000°C at a heating rate of 10°C / min, and heated at 600-1000°C for 1 hour.
[0072] In some specific embodiments of the present invention, step (5) further comprises a screening process after vacuum drying.
[0073] In some specific embodiments of the present invention, the particle size distribution of the porous carbon can be regulated by grinding into powder in step (1) and / or sieving after vacuum drying in step (5). This is well known in the art and will not be described in detail.
[0074] According to another aspect of the present invention, the present invention relates to a silicon-carbon negative electrode material, wherein the silicon-carbon negative electrode material comprises the porous carbon and nano-silicon located in the pores of the porous carbon.
[0075] In the present invention, the nano silicon is a silicon material having at least one dimension less than 100 nm. For example, at least one dimension of the nano silicon is 99 nm, 90 nm, 80 nm, 70 nm, 60 nm, 50 nm, 40 nm, 30 nm, 20 nm, 10 nm, 9 nm, 8 nm, 7 nm, 6 nm, 5 nm, 4 nm, 3 nm, 2 nm, 1.5 nm, 1 nm, 0.5 nm, 0.1 nm, 0.01 nm, etc., or other values within the range.
[0076] In some specific embodiments of the present invention, nano-silicon can be nano-silicon particles, and the crystal domain size of the nano-silicon particles is 0nm to 3nm, specifically 0.01nm, 0.1nm, 0.5nm, 1nm, 1nm, 3nm or any value between 0nm and 3nm; small particles have a higher specific surface area and a shorter diffusion path, can release pressure faster, and reduce the degree of volume expansion, which is beneficial to the improvement of coulomb efficiency. For example, a typical but non-limiting range can be nano-silicon particles with a particle size of 1-3nm.
[0077] The present invention adopts the above-mentioned porous carbon as a carrier to load nano-silicon, which can effectively improve the loading efficiency of nano-silicon, and can reserve a part of space for the volume increase caused by the expansion of silicon during the nano-scale silicon cycle process, which has the effect of alleviating the volume expansion of silicon when lithium is embedded, and can reduce the volume expansion rate of silicon-based negative electrode materials; the silicon-carbon negative electrode material of the present invention has the characteristics of high capacity and high initial efficiency, and improves the cycle stability of the battery.
[0078] In some embodiments, the mass content of nano-silicon in the silicon-carbon negative electrode material is 5% to 85%, including but not limited to 5%, 10%, 20%, 3%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 80%, 85%, etc., or a range between any two of the above. In the silicon-carbon negative electrode material of the present invention, nano-silicon has an appropriate mass content, which is more conducive to ensuring the comprehensive electrical properties of the silicon-carbon negative electrode material.
[0079] In some embodiments, the particle size Dv50 of the silicon-carbon negative electrode material of the present invention is 3 to 10 μm, including but not limited to 3 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc., or a range between any two of the above. The particle size Dv99 of the silicon-carbon negative electrode material is 10 to 25 μm, including but not limited to 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 25 μm, etc., or a range between any two of the above. The particle size Dn10 of the silicon-carbon negative electrode material is 0.5 to 5 μm, including but not limited to 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc., or a range between any two of the above. The silicon-carbon negative electrode material of the present invention has the above-mentioned suitable particle size, which is more conducive to ensuring the performance of the slurry and improving the volume energy, charge and discharge performance and cycle performance of the battery.
[0080] In some embodiments, the silicon-carbon negative electrode material of the present invention has a suitable specific surface area of 0.5 to 30 m 2 / g. In some embodiments, the specific surface area of the silicon-carbon negative electrode material includes but is not limited to 0.5 m 2 / g, 1m 2 / g, 3m 2 / g, 5m 2 / g, 10m 2 / g, 15m 2 / g, 30m 2 / g, etc., or a range between any two of the above.
[0081] In some embodiments, the tap density of the silicon-carbon negative electrode material of the present invention is 0.5 to 2 g / cm 3 In some embodiments, the tap density of the silicon-carbon negative electrode material includes but is not limited to 0.5 g / cm 3 , 0.72g / cm 3 , 0.75g / cm 3 、0.78g / cm 3 , 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 The silicon-carbon negative electrode material of the present invention has a suitable tap density, so as to obtain high capacity and high initial efficiency.
[0082] In some embodiments, the surface of the silicon-carbon negative electrode material of the present invention further includes a coating layer; the coating layer contains at least one of amorphous carbon, a fast ion conductor and a high molecular polymer, which is more conducive to improving the comprehensive electrical properties of the negative electrode material.
[0083] According to another aspect of the present invention, the present invention also relates to a method for preparing the above silicon-carbon negative electrode material, comprising the following steps:
[0084] The porous carbon is vapor-deposited in an atmosphere containing a silicon source to obtain a silicon-carbon negative electrode material.
[0085] The preparation method of the silicon-carbon negative electrode material of the present invention is simple and easy, and the silicon-carbon negative electrode material can be obtained by vapor-depositing a silicon source on porous carbon. The silicon-carbon negative electrode material obtained by the method has the characteristics of high capacity and high initial efficiency.
[0086] In some embodiments, the temperature of the vapor deposition is 300-1200°C, including but not limited to 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, etc., or any range between two values.
[0087] In some embodiments, the silicon source of the present invention includes at least one of monosilane (SiH4), trisilane, disilane, dimethylsilane, dichlorosilane, hexamethyldisilane, silicon tetrachloride, trichlorosilane, and silicon tetrafluoride.
[0088] In some embodiments, the method further comprises: coating the silicon-carbon negative electrode material to obtain a coating layer on the surface of the silicon-carbon negative electrode material, wherein the coating layer comprises at least one of amorphous carbon, a fast ion conductor and a high molecular polymer. The present invention further coats the carbon coating layer to improve the electrical properties of the silicon-carbon negative electrode material.
[0089] In some embodiments, the coating treatment temperature is 300-1200°C, including but not limited to 300°C, 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, etc., or any range between the two; the coating treatment deposition time is 20min-6h, including but not limited to 20min, 1h, 2h, 3h, 4h, 5h or 6h, etc., or any range between the two. The present invention is more conducive to obtaining a uniform, high-quality carbon coating layer by adopting appropriate coating treatment conditions, which is conducive to the electrical performance of the final negative electrode material.
[0090] In some specific embodiments, the method for preparing the silicon-carbon negative electrode material comprises the following steps:
[0091] (a) Drying mangosteen peel and grinding it into powder; stirring the powder in HCl, then washing it with deionized water until the water is colorless, and drying it; uniformly dispersing the dried mangosteen peel powder and KOH in water at a mass ratio of 1:1 to 1:4, stirring it, and then freeze-drying it to remove moisture to obtain a mixed precursor; in an argon atmosphere, rapidly heating the obtained mixed precursor in a tube furnace to 200°C at a rate of 10°C / min, then slowly heating it from 200°C to 550°C for 10 hours, then rapidly heating it to 600-1000°C at a heating rate of 10°C / min, and heating it at 600-1000°C for 1 hour to obtain a calcined product; washing the calcined product with deionized water, then vacuum drying it, and sieving it to obtain porous carbon.
[0092] (b) placing the porous carbon of step (a) in a heat treatment device for preheating at a temperature of 90 to 120°C and keeping the temperature under vacuum for 20 to 40 min; then introducing a protective gas, and then raising the temperature to 300 to 1200°C at a rate of 1 to 8°C / min, and then introducing a silicon source gas at a flow rate of 0.4 to 12 L / min for 2 to 5 h, closing the silicon source valve, and obtaining a first material.
[0093] (c) The obtained first material is heated to 300-1200° C., and a carbon source gas is introduced into the material for 20 min-6 h to obtain a silicon-carbon negative electrode material.
[0094] According to another aspect of the present invention, the present invention also relates to an electrode, comprising the porous carbon, or the silicon-carbon negative electrode material, or the silicon-carbon negative electrode material prepared by the preparation method of the silicon-carbon negative electrode material.
[0095] The electrode of the present invention comprises the porous carbon and has excellent electrical properties. The electrode comprises a current collector and a negative electrode material layer located on the surface of the current collector, wherein the negative electrode material layer contains the porous carbon or silicon-carbon negative electrode material.
[0096] According to another aspect of the present invention, the present invention also relates to a lithium ion battery comprising the electrode.
[0097] The lithium ion battery of the present invention has high capacity, high initial efficiency, excellent cycle performance and safety performance.
[0098] According to another aspect of the present invention, the present invention also relates to an electrical appliance, comprising the lithium-ion battery.
[0099] In the present invention, the electrical appliances may be, but are not limited to, mobile phones, tablet computers, laptop computers, electric toys, electric tools, battery vehicles, electric vehicles, ships, spacecraft, and the like.
[0100] The following is further explained in conjunction with specific embodiments and comparative examples.
[0101] Example 1
[0102] A method for preparing a silicon-carbon negative electrode material comprises the following steps:
[0103] S1. Preparation of porous carbon:
[0104] (1) Dry the mangosteen peel at 80°C for 24 h and grind it into powder.
[0105] (2) Stir in 1 M HCl overnight, then wash with deionized water until the water is colorless, and dry at 80 °C for 12 h.
[0106] (3) The dried mangosteen peel powder and KOH were uniformly dispersed in water at a mass ratio of 1:3, stirred overnight, and then freeze-dried to remove moisture.
[0107] (4) In an argon atmosphere, the mixed precursor was heated to 200 °C in a tube furnace at a heating rate of 10 °C / min, then heated from 200 °C to 550 °C for 10 h, then heated to 780 °C at a heating rate of 10 °C / min, and heated at 780 °C for 1 h.
[0108] (5) Finally, the calcined product was washed with deionized water, dried in vacuum at 80° C. for 12 h, and sieved to obtain the porous carbon.
[0109] The particle size D50 of the porous carbon in this embodiment is 7.6 μm, Dv99 is 22.7 μm, Dn10 is 3.1 μm, and the specific surface area is 1946 m 2 / g, pore volume is 0.91cm 3 / g, the electrical conductivity is 2.7S / mm, and its pore structure is: the pore volume of pores smaller than 2nm accounts for 94% of the total pore volume (microporosity), the pore volume of pores smaller than 0.7nm accounts for 25% of the total pore volume (microporosity), and its pore size distribution is Luan-shaped distribution.
[0110] S2. Vapor-phase silicon deposition: The porous carbon was placed in a rotary furnace, heated to 100°C, and kept warm for 30 min under vacuum. Then, nitrogen was introduced for protection. The temperature was then raised to 550°C at a rate of 5°C / min. Monosilane was introduced at a flow rate of 10 L / min for 4 h. After the reaction was completed, the silicon source valve was closed.
[0111] S3. Carbon coating: After silicon deposition is completed, the temperature is raised to 700°C, and acetylene is introduced at a flow rate of 5 L / min. The acetylene is introduced for 3 hours to obtain a silicon-carbon negative electrode material.
[0112] Example 2
[0113] The preparation method of the negative electrode material provided in this embodiment refers to that in Example 1, except that:
[0114] S1. Preparation of porous carbon:
[0115] (1) Dry the mangosteen peel at 80°C for 24 h and grind it into powder.
[0116] (2) Stir in 1 M HCl overnight, then wash with deionized water until the water is colorless, and dry at 80 °C for 12 h.
[0117] (3) The dried mangosteen peel powder and KOH were uniformly dispersed in water at a mass ratio of 1:2, stirred overnight, and then freeze-dried to remove moisture.
[0118] (4) In an argon atmosphere, the mixed precursor was heated to 200 °C in a tube furnace at a heating rate of 10 °C / min, then heated from 200 °C to 550 °C for 10 h, then heated to 650 °C at a heating rate of 10 °C / min, and heated at 650 °C for 1 h.
[0119] (5) Finally, the calcined product was washed with deionized water, dried in vacuum at 80° C. for 12 h, and sieved to obtain the porous carbon.
[0120] The particle size D50 of the porous carbon in this embodiment is 7.3 μm, Dv99 is 21.1 μm, Dn10 is 0.5 μm, and the specific surface area is 1669 m 2 / g, pore volume is 0.74cm 3 / g, the electrical conductivity is 1.9S / mm, and its pore structure is: the pore volume of pores smaller than 2nm accounts for 93% of the total pore volume (microporosity), the pore volume of pores smaller than 0.7nm accounts for 28% of the total pore volume (microporosity), and its pore size distribution is Luan-shaped distribution.
[0121] Example 3
[0122] The preparation method of the negative electrode material provided in this embodiment refers to that in Example 1, except that:
[0123] S1. Preparation of porous carbon:
[0124] (1) Dry the mangosteen peel at 80°C for 24 h and grind it into powder.
[0125] (2) Stir in 1 M HCl overnight, then wash with deionized water until the water is colorless, and dry at 80 °C for 12 h.
[0126] (3) The dried mangosteen peel powder and KOH were uniformly dispersed in water at a mass ratio of 1:2.5, stirred overnight, and then freeze-dried to remove moisture.
[0127] (4) In an argon atmosphere, the mixed precursor was heated to 200 °C in a tube furnace at a heating rate of 10 °C / min, then heated from 200 °C to 550 °C for 10 h, then heated to 700 °C at a heating rate of 10 °C / min, and heated at 700 °C for 1 h.
[0128] (5) Finally, the calcined product was washed with deionized water, dried in vacuum at 80° C. for 12 h, and sieved to obtain the porous carbon.
[0129] The porous carbon in this embodiment has a particle size D50 of 6.4 μm, a Dv99 of 18.7 μm, a Dn10 of 2.5 μm, and a specific surface area of 1911 m 2 / g, pore volume is 0.81cm 3 / g, the electrical conductivity is 2.7S / mm, and its pore structure is: the percentage of pores smaller than 2nm in the total pore volume (microporosity) is 100%, the percentage of pores smaller than 0.7nm in the total pore volume (microporosity) is 29%, and its pore size distribution is Luan-shaped distribution.
[0130] Comparative Example 1
[0131] The difference between the preparation method of the negative electrode material in this comparative example and that in Example 1 is that the porous carbon used for vapor phase silicon deposition is different. The porous carbon used in this comparative example was purchased from Jiangsu Pushida Environmental Protection Technology Co., Ltd., model PAC-A1. The remaining process parameters of vapor phase silicon deposition and carbon coating are the same as in Example 1.
[0132] The particle size D50 of the porous carbon in this comparative example is 7.2 μm, Dv99 is 23 μm, Dn10 is 3.5 μm, and the specific surface area is 1297 m 2 / g, pore volume is 0.94cm 3 / g, the electrical conductivity is 0.33S / mm, and in its pore structure, the pore volume of pores smaller than 2nm accounts for 54% of the total pore volume, the pore volume of pores smaller than 0.7nm accounts for 25% of the total pore volume (microporosity), and the pore structure of porous carbon has a peak structure.
[0133] Comparative Example 2
[0134] The difference between the preparation method of the negative electrode material in this comparative example and that in Example 1 is that the porous carbon used for vapor phase silicon deposition is different. The porous carbon used in this comparative example was purchased from Dachao Carbon Energy Co., Ltd., and the remaining process parameters of vapor phase silicon deposition and carbon coating are the same as in Example 1.
[0135] The particle size D50 of the porous carbon in this comparative example is 7.6 μm, Dv99 is 22 μm, Dn10 is 0.5 μm, and the specific surface area is 2053 m 2 / g, pore volume is 0.84cm 3 / g, the electrical conductivity is 2.92S / mm, and in its pore structure, the pore volume of pores smaller than 2nm accounts for 100% of the total pore volume, the pore volume of pores smaller than 0.7nm accounts for 33% of the total pore volume (microporosity), and the pore structure of the porous carbon has a Luan-shaped structure.
[0136] Comparative Example 3
[0137] The difference between the preparation method of silicon-carbon negative electrode material in this comparative example and that in Example 1 is that the porous carbon used for vapor phase silicon deposition is different. The porous carbon used in this comparative example was purchased from Jiangsu Pushida Environmental Protection Technology Co., Ltd., model PAC-SP40. The remaining process parameters of vapor phase silicon deposition and carbon coating are the same as in Example 1.
[0138] The particle size D50 of the porous carbon in this comparative example is 6.6 μm, Dv99 is 20.8 μm, Dn10 is 3.4 μm, and the specific surface area is 1282 m 2 / g, pore volume is 0.72cm 3 / g, the electrical conductivity is 4.3S / mm, and in its pore structure, the pore volume of pores smaller than 2nm accounts for 50% of the total pore volume, the pore volume of pores smaller than 0.7nm accounts for 21% of the total pore volume (microporosity), and the pore structure of the porous carbon has a Luan-shaped structure.
[0139] Experimental example
[0140] 1. Performance test of porous carbon
[0141] The test methods for the specific surface area, pore volume, and pore ratio <2 nm of the porous carbon of each embodiment and comparative example are as follows:
[0142] Specific surface area and pore volume: Tested according to GB / T 19587-2017. ASAP 2460 (from Micromeritics) was used for measurement, which works according to the Sorption Method with Adaptive dosing Rate (SMART method). As for reference materials, standard material GB13905 (9.01 m 2 / g, based on multi-point BET method), GB13913 (5.78m 2 / g, based on multi-point BET method) and GB13909 (specific surface area, total pore volume and pore size standard materials of mesoporous SiO2).
[0143] To reduce the dead volume, filler rods are added to the reference and sample test tubes. The test tubes are mounted on the BET device. The saturated vapor pressure of nitrogen (N2 4.0) is determined. A certain amount of sample is weighed into the glass test tube so that the test tube containing the filler rod is completely filled and the minimum dead volume is produced. To dry the sample, the sample is kept at 200°C under vacuum for 2h. After cooling, the sample weight is recorded. The glass test tube containing the sample is mounted on the measuring device. To degas the sample, it is evacuated at a selected pumping speed so that no material is sucked into the pump, reaching a final pressure of 200mTorr.
[0144] Micropore ratio (microporosity) test method: The percentage of pore volume with a pore size of less than 2 nm in porous carbon to the total pore volume is tested by nitrogen adsorption method. Nitrogen adsorption measurement is performed using ASAP 2460 instrument from Micromeritics Instruments at liquid nitrogen temperature (77.3K). Before measurement, the sample is degassed at 443K until a static vacuum of less than 0.01 Torr is reached. The adsorption potential distribution is calculated based on the adsorption isotherm using standard instrument software DFT (NLDFT) software.
[0145] The above test results of the porous carbon of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1.
[0146] Table 1 Physical parameters of porous carbon
[0147]
[0148]
[0149] The pore size distribution curve of the porous carbon in Example 1 of the present invention is as follows: Figure 1 As shown, the pore size distribution curve of the porous carbon in Example 2 is as shown in Figure 2 As shown, the pore size distribution curve of the porous carbon in Example 3 is as shown in Figure 3 As shown, it can be seen that in the porous carbon of the present invention, as the pore size increases, the pore distribution changes in a mountainous manner. In the pore size range of 1 to 2 nm, the pore size distribution curve has no intersection with the horizontal axis, and the pore size transition is relatively smooth and relaxed, that is, the pores of the porous carbon are relatively uniform. The pore size of the porous carbon of the present invention is distributed in a Luan-shaped manner, such as Figure 7 As shown, the pore size distribution is continuous and uninterrupted, the total number of pores is large, and the pore depth is basically consistent, which can reduce the local resistance caused by diameter change, facilitate the entry of silane molecules, improve the silicon loading efficiency, and help improve the electrochemical performance of silicon-carbon negative electrode materials.
[0150] The pore size distribution curve of the porous carbon in Comparative Example 1 of the present invention is as follows: Figure 4As shown, it can be seen that in the range of pore diameters of 1 to 2 nm, the pore diameter curve and the horizontal axis have multiple intersections. As the pore diameter increases, the pore distribution changes in a peak-to-valley manner, and the pore diameter transition is relatively steep, that is, the micropores are uneven and have significant diameter variation characteristics. The schematic diagram of the peak-shaped pores of the porous carbon of Comparative Example 1 is shown in Figure 8 As shown, the pore size distribution is discontinuous and the total number of pores is insufficient. When the pores are deeper and the pore diameter is smaller, the resistance that nanosilicon needs to overcome for entry is greater and the relative distance that can diffuse (compared with the pore depth) is shorter. Therefore, the utilization rate of the pores is also lower, which is not conducive to the loading of silicon materials and the performance of silicon-carbon negative electrode materials.
[0151] The porous carbon in comparative example 2 of the present invention was purchased from Dachao Carbon Energy Company. The pore size distribution curve of the porous carbon is shown in FIG. Figure 5 As shown, the percentage of the pore volume of pores with a pore diameter less than 0.7 nm to the total pore volume is relatively high.
[0152] The porous carbon in comparative example 3 of the present invention was purchased from Jiangsu Pushida Environmental Protection Technology Co., Ltd. The pore size distribution curve of the porous carbon is shown in FIG. Figure 6 As shown, the specific surface area is relatively low and the microporosity is low.
[0153] 2. Performance test of silicon-carbon negative electrode materials
[0154] The particle size, specific surface area, tap density, silicon content and silane utilization rate of the silicon-carbon negative electrode materials of each embodiment and comparative example were tested as follows:
[0155] Specific surface area test: The specific surface area was tested using the BET method according to GB / T 19587-2017, including: Nitrogen adsorption measurements were performed using the ASAP 2460 instrument from Micromeritics Instruments at liquid nitrogen temperature (77.3K). Before the measurement, the sample was degassed at 443K until a static vacuum of less than 0.01 Torr was reached. The adsorption point distribution was calculated based on the adsorption isotherm using the standard instrument software DFT (NLDFT) software. In order to reduce the dead volume, filler rods were added to the reference test tube and the sample test tube (the specific test method is the same as the test method for the specific surface area of porous carbon).
[0156] Particle size test: Malvern 3000 equipment is used for testing according to the national standard GB / T 19077-2016.
[0157] Tap density test: Tested using Dandong Better BT313 tap density tester, tested according to national standard GB / T 24533-2019.
[0158] Silicon content test: The silicon content is measured by calcining at 1000℃ in air for 1 hour using a thermogravimetric analyzer to completely oxidize the carbon and make it lose weight, and to completely convert the silicon into silicon dioxide. The weight of the added oxygen is then used to calculate the silicon content in the silicon-carbon material. The details are as follows:
[0159] (1) Weigh about 2 g of silicon-carbon material, with the actual mass recorded as m0; and place it in a crucible with a mass of m1;
[0160] (2) Place the crucible in a tube furnace or muffle furnace, continue to pass compressed air, raise the temperature to 600°C at 10°C / min, hold for 1 hour, then raise the temperature to 1000°C at the same rate and hold for 1 hour;
[0161] (3) After cooling naturally to room temperature, take out the crucible and weigh its mass m2;
[0162] (4) Calculate Si content Si% = (m2-m1) × MSi÷MSiO2÷m0×100%;
[0163] Note: MSiO2 is the relative molecular mass of SiO2, 60.084 g / mol; MSi is the relative molecular mass of Si, 28.0855 g / mol.
[0164] Silane utilization % = [received material amount (g) × silicon content (%)] / [volume of silane introduced (L) × silane density (g / L)].
[0165] The performance test results of silicon-carbon negative electrode materials are shown in Table 2.
[0166] Table 2 Performance test results of silicon-carbon negative electrode materials
[0167]
[0168] As shown in Table 2, the silicon-carbon negative electrode materials obtained by the methods of the embodiments of the present invention have suitable particle size, specific surface area, tap density and silicon content, and the silane utilization rate is high, at 93% or above. The silane utilization rate of the silicon-carbon negative electrode materials obtained in Comparative Examples 1 to 3 is relatively low.
[0169] 3. Battery performance test results
[0170] The silicon-carbon negative electrode materials of each embodiment and comparative example are respectively prepared into button-type half-cells, comprising the following steps:
[0171] The active material, SP, CNT and PAA glue were mixed in a mass ratio of 80:9:1:10, made into a slurry with deionized water, evenly coated on a copper foil, and vacuum dried at 80°C for 24 h to obtain the experimental battery negative electrode sheet. The lithium sheet was used as the counter electrode, and 1.1 mol / L LiPF6 electrolyte was used. The solvent was a four-component mixed solvent, ethylene carbonate (EC): vinylene carbonate (VC): dimethyl carbonate (DMC): fluoroethylene carbonate (FEC) = 1:1:1:1 (volume ratio). A polypropylene microporous film was used as the separator and assembled into a CR2025 button half-cell in a vacuum glove box.
[0172] The battery performance test method is: use a battery test system (half-battery test American Arbin multi-channel battery test system, German Braun Company Labstar (1200 / 780) glove box) to test the capacity and the first charge and discharge efficiency (first efficiency).
[0173] The test steps are: 0.1C DC to 5mV, let stand for 5min; 0.02C DC to 5mV, let stand for 5min; 0.01C DCto 5mV, let stand for 5min; 0.1C CC to 0.8V, 0.1C CC to 2V.
[0174] The performance test results of the battery are shown in Table 3.
[0175] Table 3 Battery performance test results
[0176] Group 1.5V discharge capacity (mAh) 1.5V Efficiency (%) Example 1 2135 92.7 Example 2 1992 90.8 Example 3 2022 91.5 Comparative Example 1 1680 78.2 Comparative Example 2 1922 89.8 Comparative Example 3 1890 86.1
[0177] The pore size distribution of the porous carbon of the present invention is a Luan-shaped distribution, with suitable microporosity, specific surface area, pore volume, and particle size. The silicon-carbon negative electrode material prepared therefrom has the characteristics of high capacity, high initial efficiency, and low silicon expansion rate. As can be seen from Table 3, the obtained battery has excellent discharge capacity and efficiency, with a 1.5V discharge capacity of more than 1990mAh and a 1.5V efficiency of more than 90%. The silicon-carbon negative electrode material of Comparative Example 1 is prepared from porous carbon with a peak-shaped distribution pore structure, and the obtained battery has low capacity and poor efficiency, with a 1.5V discharge capacity of 1680mAh and a 1.5V efficiency of 78.2%. Comparative Examples 2 to 3 use conventional porous carbon to prepare silicon-carbon negative electrode materials and batteries, and the capacity and efficiency of the obtained batteries are lower than those of Example 1.
[0178] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A porous carbon, characterized in that The porous carbon includes micropores, and the percentage of the pore volume of the micropores in the total pore volume is greater than or equal to 85%. In a pore distribution curve obtained by a nitrogen adsorption method, in which the abscissa is the pore diameter and the ordinate is the differential pore volume dV / dW, the porous carbon has a pore diameter range of 1 to 2 nm, and the differential pore volume dV / dW>0.05 cm 3 ·g -1 ·nm -1 .
2. The porous carbon according to claim 1, characterized in that Contains at least one of the following features (1) to (3): (1) The porous carbon has at least one peak in the range of pore diameter of 1 to 2 nm; (2) The porous carbon has at least one peak-valley in the pore diameter range of 1 to 2 nm, and the differential pore volume dV / dW corresponding to the lowest point of the peak-valley is greater than 0.1 cm 3 ·g -1 ·nm -1 ; (3) In the porous carbon, the percentage of pore volume with pore diameter less than 0.7 nm in the total pore volume is less than 30%; (4) The pore volume of the porous carbon is 0.7 to 1.2 cm 3 / g.
3. The porous carbon according to claim 1, characterized in that Contains at least one of the following features (1) to (5): (1) The specific surface area of the porous carbon is 1500 to 2500 m 2 / g; (2) The particle size Dv50 of the porous carbon is 3 to 10 μm, the particle size Dv99 of the porous carbon is 10 to 25 μm, and the particle size Dn10 of the porous carbon is 0.5 to 5 μm; (3) The tap density of the porous carbon is 0.3 to 0.5 g / cm 3 ; (4) The powder conductivity of the porous carbon is 0.5 to 10 S / mm; (5) The mass content of elemental oxygen in the porous carbon is less than 2%.
4. A silicon-carbon negative electrode material, characterized in that: The silicon-carbon negative electrode material comprises the porous carbon according to any one of claims 1 to 3 and nano-silicon located in the pores of the porous carbon.
5. The silicon-carbon negative electrode material according to claim 4, characterized in that: Contains at least one of the following features (1) to (5): (1) The mass content of the nano-silicon in the silicon-carbon negative electrode material is 5 to 85%; (2) The particle size Dv50 of the silicon-carbon negative electrode material is 3 to 10 μm, the particle size Dv99 of the silicon-carbon negative electrode material is 10 to 25 μm, and the particle size Dn10 of the silicon-carbon negative electrode material is 0.5 to 5 μm; (3) The specific surface area of the silicon-carbon negative electrode material is 0.5 to 30 m 2 / g; (4) The tap density of the silicon-carbon negative electrode material is 0.5 to 2 g / cm 3 ; (5) The surface of the silicon-carbon negative electrode material also includes a coating layer; the coating layer contains at least one of amorphous carbon, a fast ion conductor and a high molecular polymer.
6. The method for preparing the silicon-carbon negative electrode material according to claim 4 or 5, characterized in that: The following steps are involved: The porous carbon is vapor-deposited in an atmosphere containing a silicon source to obtain the silicon-carbon negative electrode material.
7. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: Also includes: The silicon-carbon negative electrode material is subjected to coating treatment to obtain a coating layer on the surface of the silicon-carbon negative electrode material, wherein the coating layer contains at least one of amorphous carbon, a fast ion conductor and a high molecular polymer.
8. An electrode, characterized in that: The invention comprises the porous carbon as described in any one of claims 1 to 3, or the silicon-carbon negative electrode material as described in any one of claims 4 to 5, or the silicon-carbon negative electrode material prepared by the preparation method of the silicon-carbon negative electrode material as described in any one of claims 6 to 7.
9. A lithium ion battery, characterized in that: Comprising the electrode according to claim 8.
10. An electrical appliance, characterized in that: Includes the lithium ion battery as claimed in claim 9.
Citation Information
Patent Citations
Lithium secondary battery
CN102714301A
Porous carbon material and preparation method and application thereof
CN103420353A
Negative electrode material, preparation method thereof and lithium ion battery
CN117317205A
Ultramicroporous hard carbon material as well as preparation method and application thereof
CN117985686A
Porous carbon material and preparation method thereof, silicon carbon material, secondary battery and electronic equipment
CN118637606A
Cited By
Porous carbon, and silicon-carbon negative electrode material and preparation method therefor and use thereof
WO2026067785A1